Analisis Lifestyle Exposure Theory terhadap Korban dari Pinjaman Online Ilegal melalu Aplikasi “Pinjaman Now” - Gadis Febri Nuraini; Muhammad Zaky (Universitas Budi Luhur, 2023)
The online loan trap (pinjol) that is now rife with victims is driven by the lifestyle of some people beyond their capabilities. It may be that the people who are trapped in financiers at first are not motivated by urgent needs or economic factors, but because of their own consumptive lifestyle. People who emphasize alifestyle beyond the limits of their financial means cause their economy to be bigger than the stake. It is at this point that they can be tempted when there is an offer of illegal loans in the form of easy loans with only an ID card without meeting the creditors of the loan, low literacy related to financial technology and digital technology companies is also considered to be the dominant factor in the fall of people in the illegal loan trap. With its considerable potential, due to the emergence of many online loan services, both registered (legal) and unregistered (illegal). However, the emergence of illegal online loan services has a negativeimpact, especially financial losses for the community as consumers of these services. Therefore, the purpose of this paper is to find out the reasons why someone prefers to use an illegal online loan when they need money quickly, find out how the process of someone getting caught in an illegal loan and what efforts are needed to overcome illegal online loan services. With reference to the negative impact caused by illegal online loan services, efforts that can be made include cooperation between the Indonesian Consumers Foundation (YLKI), the Financial Services Authority (OJK), Kominfo and the Police under supervision; increasing community digital literacy; the need for regulations related to consumer protection; and evaluation of mechanisms; company registration. The role of the Government is urgently needed insupporting OJK and YLKI to immediately address illegal online loan services in a special regulation.